1994
DOI: 10.1093/ndt/9.6.668
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium-related osteodystrophy and desferrioxamine treatment: role of phosphorus

Abstract: We investigated (1) the prevalence of aluminium overload among 96 patients with symptomatic bone disease haemodialysed from 1987 to 1989 in the Sao Paulo area, Brazil; (2) the effect of 6 months desferrioxamine (DFO) treatment (1-2g/week). All patients underwent a first bone biopsy. Aluminium overload (extent of stainable bone aluminium more than 20% trabecular surface) was observed in 74 of 96 patients. Forty overloaded patients were divided into patients with high bone formation rate (BFR) (group 1; n = 17) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…This result suggested that the removal of aluminum partially restores the gland's sensitivity. This finding is also supported by another clinical study carried out after 6 months of continuous deferoxamine administration [19].…”
Section: Bone Remodeling and Renal Osteodystrophysupporting
confidence: 66%
See 1 more Smart Citation
“…This result suggested that the removal of aluminum partially restores the gland's sensitivity. This finding is also supported by another clinical study carried out after 6 months of continuous deferoxamine administration [19].…”
Section: Bone Remodeling and Renal Osteodystrophysupporting
confidence: 66%
“…Aluminum toxicity, the main cause of low-bone-turnover osteomalacia in the 1970s and 1980s, is now better managed in most developed countries [16]. In other areas of the world [17][18][19], however, aluminum toxicity remains a major challenge. The change in the pattern of aluminum exposure alone cannot explain the increase in the prevalence of adynamic bone disease.…”
Section: Bone Remodeling and Renal Osteodystrophymentioning
confidence: 99%
“…43 O controle do tratamento pode ser feito por meio do teste de desferroxamina ou da biópsia óssea. [44][45][46] …”
Section: Racionalunclassified
“…The bone specimens were fixed in 70% ethanol and processed for histomorphometry as previously described (7). For aluminum quantification, the material was stained with aurin tricarboxylic acid.…”
Section: Bone Histomorphometrymentioning
confidence: 99%